Stimulation of Transformational Leadership in Teachers' Intellectuals at MTsN 1 and MTsN 2 Tulungagung - Mustofa, Asrori; Qomar, Mujamil; Tanzeh, Ahmad; Aziz, Abd.; Akhyak, Akhyak; Maftukhin, Maftukhin (Technium Social Sciences Journal, 2021)
Transformational leadership has a significant impact on the progress and development of educational institution achievements. Effective leadership of madrasah principals can create the realization of various progress and achievements. The substance of intellectual stimulation behavior is a form of effort to increase intelligence, rationality, and thorough problem solving. Transformational leaders need to invite members of educational organizations to see problems from a new, more comprehensive, and broad perspective, so that problems are not framed partially. This study uses a qualitative approach, the type of case study with a multi-case design. The results showed that transformational leadership in developing resources by strengthening intellectual stimulation, TUSI distribution, preparing leader regeneration, decisive action, giving recognition, rewards and solving problems that hinder transformation.